No place for dying : hospitals and the ideology of rescue - Chapple, Helen Stanton (Left Coast Press, 2010)
This book shows how dying is a management problem for hospitals, occupying space but few billable encounters and of little interest to medical practice or quality control. An anthropologist and bioethicist with two decades of professional nursing experience, Helen Chapple goes beyond current work on hospital care to present fine-grained accounts of the clinicians, patients, and families who navigate this uncharted, untidy, and unpredictable territory between the highly choreographed project of rescue and the clinical culmination of death.